Modulating the Antifungal Activity of Antimycotic Drugs with Farnesol - N. P. Sachivkina; A. N. Senyagin; I. V. Podoprigora; D. G. Brown; V. V. Vissarionova (Разработка и регистрация лекарственных средств)
Introduction. Clinical strains of microorganisms, including opportunistic yeast-like fungi (YLF) of the genus Candida, are resistant to currently used antifungal drugs. In this regard, the search for alternative ways to potentiate the activity of antimicrobial agents in relation to the infectious agent is an important and relevant area of research. The study of combinations of existing antimycotic drugs and a medicinal extract of plant origin – farnesol – is one of the promising approaches in the fight against resistant strains of YLF genus Candida. In our previous studies, farnesol has been shown to exhibit relative activity against YLF Candida albicans biofilms. In this study, we used 6 clinical isolates and one museum strain YLF C. albicans to study the effect of farnesol on the antifungal activity of antimycotic drugs.Aim. To prove that farnesol can increase the antifungal activity of certain antimycotics.Materials and methods. To determine the sensitivity of 7 strains of YLF C. albicans to the antimycotic drugs "Nystatin" (NYS 50 µg), "Ketoconazole" (KET 10 µg), "Clotrimazole" (CTR 10 µg), "Amphotericin B" (AMB 10 µg), "Voriconazole" (VRC 10 µg) disk diffusion test was used. A solution of farnesol in concentrations of 100, 50 and 25 µM in a volume of 25 µl was applied to the disk with the antimycotic drug. Sterile physiological (PhS) solution was used as a control (pH 7.0; V = 25 µl).Results and discussion. In 34.3 % of of experiments we can talk about the modulating effect of farnesol solutions on the antifungal activity of antimycotic drugs. In all these cases, the sensitivity of YLF C. albicans to the antimycotic drug increases.Conclusion. The results of this study provide useful information for understanding the mechanism of QS-molecules action with antifungal activity, as well as they are the basis for the practical application of some QS-molecules in the treatment of infectious diseases caused by YLF of the genus Candida. The study demonstrates that farnesol can be recommended as an active substance that improves the sensitivity of YLF Candida to antimycotic drugs, especially in the case of multi-resistant strains Candida.